A Comparison of Methods for Identifying and Quantifying Ice Rafted Debris on the Antarctic Margin. Issue 4 (15th April 2022) - McKay, Robert; Albot, Olga; Dunbar, Gavin B.; Lee, Jae Il; Lee, Min Kyung; Yoo, Kyu‐Cheul; Kim, Sunghan; Turton, Nikita; Kulhanek, Denise; Patterson, Molly; Levy, Richard
Abstract: Quantification of ice rafted debris (IRD) abundances in deep‐sea records is often used as a key proxy for identifying links between ice sheet instability and the oceanic overturning circulation. There currently exist multiple methods to determine IRD content in deep‐sea sediment cores. The preference for a given method is often determined by the accessibility to core material and destructive nature of some methods. While many studies have discussed the caveats between linking IRD to ice sheet dynamics, the uncertainties relating to the methodological approaches are often not considered in the interpretation or comparisons between different IRD datasets, particularly in the Antarctic. To address this, we compare three independent methodologies of obtaining IRD abundances and also discuss how different approaches will affect determinations of mass accumulation rates (MARs). The three methodologies we examine include: counting clasts >2 mm in x‐radiographs; the sieved weight percentage of the medium‐to‐coarse sand fraction (250 μm–2 mm); and volumetric estimates of the >125 μm sand fraction using laser diffraction particle size analysis. The x‐radiograph and sieve methods produced comparable results, while the laser particle size analysis, although showing comparable long‐term signals at most locations, in general has lower correlation to the other two methods and therefore a higher potential to obtain a noisy signal. We discuss the caveats associated with all methods, and emphasize that a combination of multiple methods should ideally be employed when assessing if a core is suitable for IRD study, and if sand or gravel fractions are accurately reflecting contents of IRD. Plain Language Summary: Ice rafted debris (IRD) records in the deep sea are fundamental indicators of past ice sheet change. However, using different methods to quantify IRD abundance in the Antarctic has the potential to produce conflicting results. We assess the role that methodological approaches may account for such differences, through a comparison of three commonly used methods. Key Points: A comparison of three methods to determine ice rafted debris (IRD) abundances in Antarctic sediment cores was undertaken X‐radiograph (>2 mm), sieve (250 μm–2 mm), and laser (125 μm–2 mm) based methods produced comparable results, but with notable differences All approaches have caveats and require independent lines of evidence to rule out deposition by other processes